2012
DOI: 10.1260/0266-3511.27.2-3.81
|View full text |Cite
|
Sign up to set email alerts
|

Design Aspects of a Deployable Tensegrity-Hollow-rope Footbridge

Abstract: Tensegrity structures are composed of cables and struts in a pre-stressed self-equilibrium. Although tensegrity first appeared in the 1950s, it is seldom used in civil engineering. This paper focuses on the design aspects of a deployable tensegrity-hollow-rope footbridge. Deployment is usually not a critical design case for traditional deployable structures. However, for tensegrity systems deployment may be critical due to the actuation required. In this paper, deployment is investigated in a general design fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…deployability. Rhode-Barbarigos et al (2012b) then studied several deployment methods and showed that utilizing springs, inspired from (Schenk et al 2007), and clustered-cables reduces the number of actuators required for controlled deployment. Bel Hadj Ali et al (2011) proposed an analysis method for clustered tensegrity structures through a modified dynamic relaxation algorithm.…”
Section: The Tensegrity Ring Footbridgementioning
confidence: 99%
See 1 more Smart Citation
“…deployability. Rhode-Barbarigos et al (2012b) then studied several deployment methods and showed that utilizing springs, inspired from (Schenk et al 2007), and clustered-cables reduces the number of actuators required for controlled deployment. Bel Hadj Ali et al (2011) proposed an analysis method for clustered tensegrity structures through a modified dynamic relaxation algorithm.…”
Section: The Tensegrity Ring Footbridgementioning
confidence: 99%
“…Two types of DR analyses are conducted to compare the test results with those from experimental tests. Numerical analysis with design stresses includes the values from Rhode-Barbarigos et al (2012b). Numerical analyses with measured cable loads are performed through introducing values that were obtained from measurements taken from the physical model.…”
Section: Deploymentmentioning
confidence: 99%
“…Changing cable lengths allows passing from one equilibrium configuration to another using finite mechanisms, while ensuring stability and stiffness (Rhode-Barbarigos et al, 2012b). The module has a height of 1m and a width of 0.87 m. To fold the simplex to half of its height, the length of horizontal cables has to increase while the length of vertical cables has to decrease.…”
Section: A Structurally Integrated Adaptive Tensegrity Structurementioning
confidence: 99%
“…Adaptive modules with multiple actuators (such as servomotors or hydraulic pistons) may require perfect synchronization, to avoid residual stresses building up, in addition to well-defined maintenance and replacement schemes, to eliminate large out-of-operation costs. From a design perspective, the engineering of such shape shifting modules is often dictated by practical hinge and actuator related constraints such as allowable forces, available sizes and energy consumption [44] rather than energy related performance criteria.…”
Section: Adaptive Enclosuresmentioning
confidence: 99%